2018
DOI: 10.18203/2394-6040.ijcmph20185265
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence and determinants of cessation of exclusive breastfeeding among primi-para rural Indian mothers

Abstract: Background: Breast milk is first, natural and nutritious food for newborn that promote sensory and cognitive development as well as protect against infectious and chronic diseases. The aim and objective of the study was to estimate the prevalence and to point out determinants of cessation of exclusive breastfeeding among rural primi-para mothers.Methods: This is a hospital based cross sectional study conducted at rural tertiary health centre located Western Maharashtra, India in the month of November-December … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
3
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 11 publications
2
3
0
Order By: Relevance
“…(17.24-25.76). The magnitude in this study was in line with the study conducted in India (22.85%) [28] and slightly lower than Southeast Ethiopia (28.7%) [24], Tigray (29.8%) [27], and Canada (28.4%) [31]. This slight difference could be t these studies were community-based and conducted before four years of this study and the study conducted in Canada was longitudinal.…”
Section: Obstetrics and Gynecology-relatedsupporting
confidence: 87%
See 1 more Smart Citation
“…(17.24-25.76). The magnitude in this study was in line with the study conducted in India (22.85%) [28] and slightly lower than Southeast Ethiopia (28.7%) [24], Tigray (29.8%) [27], and Canada (28.4%) [31]. This slight difference could be t these studies were community-based and conducted before four years of this study and the study conducted in Canada was longitudinal.…”
Section: Obstetrics and Gynecology-relatedsupporting
confidence: 87%
“…EBF has also great benefits for maternal health outcomes like reducing the risk of breast and ovarian cancer, type two diabetes, postpartum depression, and have a long duration of amenorrhea or as a natural family planning method [16]. Studies showed that factors like younger mothers [17][18][19], low level of educational status [18][19][20][21], mothers who smoke [17,18], low parity [19,[21][22][23], employed mothers [24,25], breast problem (cracked nipple) [23], initiate of breastfeeding after one hour and had no antenatal care (ANC) visits [26], had no postnatal care (PNC) visits [26,27], and cesarean delivery [25,28] are some of the independent factors that push mothers to give up exclusive EBF.…”
Section: Introductionmentioning
confidence: 99%
“…A mother living in nuclear family was less likely to practice exclusive breast feeding. The finding is in parallel with the study done in rural Indian mothers [48] in which mothers from nuclear family had high risk of cessation of exclusive breastfeeding than mothers from joint family. This might be because mothers from nuclear family lack support from members of extended family.…”
Section: Discussionsupporting
confidence: 83%
“…32 In this, the median time to cease EBF was higher than studies revealed from Indonesia, 33 Australia, 34 Kinshasa, 35 Botswana, 36 Colombia, 37 and Saudi. 38 The rate of early EBF discontinuation was 45.8%, which was higher than the studies revealed from southern Ethiopia 30.4%, 39 northwest Ethiopia 21.5%, 40 northeastern pastoralist parts of Ethiopia 35.5%, 12 Addis Ababa 42.4%, 41 mini Ethiopian demographic health survey 41%, 10 Taiwan 40.1%, 42 Kinshasa 2.8%, 35 India 22.85%, 43 Indonesia 21.3%, 33 and Kenya 2%. 44 This finding was lower than the study revealed from southern Ethiopia 48%, 45 Dukem Central Ethiopia 75.7%, 46 Nepal 50.5%, 47 Tanzania 68.7%, 48 Saudi 60%, 49 and Australia 49%.…”
Section: Discussionmentioning
confidence: 71%